An Approximate Design Technique for Microstrip Parallel-Coupled Band-Pass Microwave Filter - Ambrosio, Raymond Gerard O. (Philippine Engineering Journal, 2021)
An approximate design technique is presented for parallel coupled bandpass filter in microstrip form. Both computational and graphical forms together with simulation software are used to optimize the design. Due to the use of several graphs and approximations, an average of 3% deviation from the computed to the final simulated design was noticed.